Desenvolvimento de aplicativo para dimensionamento de dentes de engrenagens cilíndricas de dentes retos e helicoidais - Tom, Thiago Bueno (2021)
This document describes the steps of the development of a spur gears sizing application for Web and Android platforms. The literature references used for the calculations of the App are mentioned in this document, as well as the standard for the parameters utilized. The application was developed in Javascript and its structure is composed by calculation steps for the design of spur gear, being these: Tooth Geometry, Load, Root and Surface Tension Analysis, Surface Fatigue Resistance and Safety Coefficient. The software also has a section for theorical review, exposing all equations and concepts utilized. All results obtained by the App are referenced to cylindrical spur gears in accordance to the AGMA standard and parameters linked to the available literatures. The results can be utilized as guide to problems solve, small gears projects, 3D printable files or CAD files.